Littoral cell angioma of the spleen - Santos, Vitorino Modesto (Revista de Medicina e Saúde de Brasília, 2015)
<span style="font-size: 12.0pt; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: ";Times New Roman";; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Due to rarity, etiological factors and biological behaviour of littoral cell angioma of the spleen are not well understood. Therefore, additional comments are herein addressed about case studies in which associations with other entities may suggest the possibility of shared etiopathological relationships. This might be useful to enhance the awareness and suspicion index among primary care health workers.